2021
DOI: 10.31742/ijgpb.81.1.13
|View full text |Cite
|
Sign up to set email alerts
|

New hyper-variable SSRs for diversity analysis in mango (Mangifera indica L.)

Abstract: Whole genome sequence in mango offers unprecedented opportunities for genomics assisted crop improvement via enabling access to genome-wide genetic markers. In the present study, simple sequence repeats (SSRs) were predicted from genome sequence of mango. Based on the SSR length (? 50 bp), highly-variable mango SSRs (MSSRs) were sorted. A sub-set of 129 MSSRs was validated on a set of 24 diverse mango genotypes yielding marker validation and polymorphism of 88.96 and 85.27 per cent, respectively. One hundred a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…SSR markers have been widely used to differentiate mango cultivars and identify genetic diversity [11,20], distinguish some synonymous (identical SSR genotypes with different cultivar names) and homonymous (different SSR genotypes with the same cultivar name) accessions [24], genetic relatedness [10] and so on. All these SSR markers will be used in the future studies of genetic diversity, genetic map construction and marker-assisted selection and utilized for breeding programs in mango.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SSR markers have been widely used to differentiate mango cultivars and identify genetic diversity [11,20], distinguish some synonymous (identical SSR genotypes with different cultivar names) and homonymous (different SSR genotypes with the same cultivar name) accessions [24], genetic relatedness [10] and so on. All these SSR markers will be used in the future studies of genetic diversity, genetic map construction and marker-assisted selection and utilized for breeding programs in mango.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, SSR uorescent labeling technology has been developed and successfully applied to variety identi cation of grape [13], bayberry [14], watermelon [15] and other crops [16,17] due to its high e ciency, accuracy, sensitivity and automation. At present, only a few literatures have reported the application of SSR uorescent labeling technology to identify the authenticity of mango hybrids [18], genetic diversity and genetic relatedness of cultivars [19][20][21], con rmation of maternal or zygotic origin of embryogenic cultures [22]. In this study, F 1 hybrid population of 'Jinhuang' and 'Renong No.1' were used as experimental materials.…”
Section: Introductionmentioning
confidence: 99%
“…146 Srivastav et al demonstrated that 110 hyper-variable SSR markers were useful in discriminating mango germplasm and further proposed that these SSRs can serve for mapping of QTLs in mangoes. 168 Recent studies on the whole genome of Philippine mango species revealed the genome-wide variants (SNPs and InDels) including putative genes involved in mango fruit development, disease resistance, and economically important traits. 169 ■ CONCLUSIONS AND FUTURE PROSPECTIVE Improvement in fruit nutritional content and maintaining postharvest storage quality are key aspects of mango production.…”
Section: ■ Proteome Analysis Of Mango Fruitsmentioning
confidence: 99%
“…A set of genetic markers including with precise analysis methods will become valuable materials for mango breeders, which leads to the identification of regions in the genome that are associated with economically important traits beneficial for marker assisted selection in mangoes . Srivastav et al demonstrated that 110 hyper-variable SSR markers were useful in discriminating mango germplasm and further proposed that these SSRs can serve for mapping of QTLs in mangoes . Recent studies on the whole genome of Philippine mango species revealed the genome-wide variants (SNPs and InDels) including putative genes involved in mango fruit development, disease resistance, and economically important traits …”
Section: Molecular Genetic Approachesmentioning
confidence: 99%
“…Diversity studies will allow a wider understanding on the genome accessions with variable fruit characters and their origins. As the sequencing technologies improved, the generation of genomic knowledge of fruit crops progressed from application of molecular markers for genetic diversity analysis [ 214 , 215 ] and DNA fingerprinting [ 216 ] to the generation of high throughput sequencing based SNPs, TRAPs (Target Region Amplification Polymorphism) and SSR markers [ 217 , 218 ]. SNP genotyping [ 219 ] was developed based on transcriptome and whole genome sequence information in mango and banana.…”
Section: Genomic Assisted Breeding Strategies In Tropical Fruit Cropsmentioning
confidence: 99%